Acute Myocardial Infarction in a Young Lady with Mitral Stenosis – Uncommon Presentation of a Common Problem - Bhuiyan, AKM Mohiuddin; Hasan, ATM Iqbal; Rahman, Md Mukhlesur; Saha, Partha Pratim (University Heart Journal, 2020)
Chronic rheumatic heart disease is the major contributor of valvular heart disease in this subcontinent. It can affect all the four valves. Among them mitral valve is affected most of the time. Involvement of the mitral valve could be presented in various nonspecific way like chest pain, palpitation, shortness of breath, difficulty in swallowing, change in voice and so on. There are few causes behind the chest pain. Myocardial infraction is one of the important cause. University Heart Journal Vol. 17, No. 1, Jan 2021; 76-78